Town planning. The basics. - Hall, Tony (Routledge, 2020)
The planning of urban and rural areas requires thinking about where people will live, work, play, study, shop and how they will get about the place, and to devise strategies for long time periods. This book provides a general introduction to the components of urban areas, including housing, transportation and infrastructure, and health and environment, showing how appropriate policies can be developed. Explaining planning activity at different scales of operation, this book distinguishes between the "big stuff", the grand strategy for providing homes, jobs and infrastructure; the "medium stuff", the design and location of development; and the "small stuff" affecting mainly small sites and individual households. Planning as an activity is part of a complex web stretching way beyond the planning office, and this book provides an overview of the many components needed to create a successful town. It is invaluable to anyone with an interest in planning, from students learning about the subject for the first time to graduates thinking about embarking on a career in planning, to local councilors on planning committees and community boards.
Keywords: Stadtplanung; Städtebau; Stadtentwicklungsplanung; Stadtgestaltung; Einführung